(3JQJjH aJGhi GdJbi GdSHcjs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3ajgeG ef UaO aj QHjY GdBNQ ef (B43 (3hba HdHGf GdLhcfOGQ GdGKfj aj GdefUhQj eMOG hChbGa Ydi eUGdMgs
(3BNQgG (B:s
(3GdeTJQj hCbdHhgG ebGe CjOjge HGNJjGQge aJTeQ jO GdeTJQj GdJj CbGehgG ebGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdTGaYjs